Development of a Methodology for Assessing the Technical Level of Cultural Heritage Objects in Construction - Liubov Lisienkova; Tatyana Shindina; Tatiana Lisienkova (Civil Engineering Journal, 2021)
Cultural objects (building and construction) that are considered as the most valuable segment of real estate in terms of historical heritage usually evaluated only by monetary aspects. Not concreteness of the approaches to the determination of the historical heritage objects leads to the fact that its original value often remains unread, the assessment has subjective character, reflects the values of certain time frame and place. Therefore, for the purpose of determination of value of the historical heritage objects, there is need for the creation of the unified classification system of their assessment. Thus, this research is considered to be very relevant. The paper investigates intangible factors that affect the evaluation of cultural heritage objects in construction. In the work a system of value indicators, which take into account not only tangible indicators but also the intangible value of cultural heritage objects, has been developed. Developed indicators system makes it possible to evaluate the historical and cultural value of real estate objects quite objectively on the contrary to common methods which deal only with monetary aspects of market price of such objects. A methodology for a comprehensive evaluation of cultural heritage objects has been formed as well. This methodology is based on both the traditional comparative approach and the system of value indicators. As a result, suggested integrated approach has been proven to provide fair evaluation of both the tangible and intangible characteristics and improve the quality of cultural heritage objects assessment process. Doi: 10.28991/cej-2021-03091680 Full Text: PDF